2019
DOI: 10.1142/s0217732320500315
|View full text |Cite
|
Sign up to set email alerts
|

Spin-0 system of DKP equation in the background of a flat class of Gödel-type spacetime

Abstract: In this paper, we investigate the Duffin-Kemmer-Petiau (DKP) equation for spin-zero system of charge-free particles in the background of a flat class of Gödel-type space-times, and evaluate the individual energy levels and corresponding wave-functions, in details.keywords: Gödel-type space-times, relativistic wave equations, energy spectrum, wave functions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…That fact implies that there is no channel for spontaneous boson-antiboson creation. We have shown that for ω → 0, zero oscillator frequency, the energy eigenvalues reduces to the result obtained in [32]. A special case corresponds…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…That fact implies that there is no channel for spontaneous boson-antiboson creation. We have shown that for ω → 0, zero oscillator frequency, the energy eigenvalues reduces to the result obtained in [32]. A special case corresponds…”
Section: Discussionmentioning
confidence: 54%
“…We have defined the tetrad basis e µ (a) , e (a) µ for the space-time in [32] which must satisfy the following relation…”
Section: Dkp Oscillator In a Gödel-type Space-timementioning
confidence: 99%
See 1 more Smart Citation
“…. Consider the following stationary space-time [50] (see [5,12,13,44,51]) in the Cartesian coordinates ðx 0 = t, x 1 = x, x 2 = y, x 3 = zÞ which is given by…”
Section: Bosonic Charged Particle: the Kg Equationmentioning
confidence: 99%
“…The relativistic quantum motion of spin-0 particles in a flat class of Gödel-type space-time was studied in [12]. The study of the spin-0 system of the DKP equation in a flat class of Gödel-type space-time was studied in [13]. In all the above systems, the influence of topological defects and vorticity parameter characterizing the space-time on the relativistic energy eigenvalues was analyzed.…”
Section: Introductionmentioning
confidence: 99%